Tomas Aquinas and the five ways to the existence of God: reflections about his life and his theological and philosophical thought - Maurial, Iván (2015)
In this article, a brief vision of the life and philosophy of Thomas Aquinas is introduced in three general steps. Our first intent is to make known the peculiarites of his work considering his personal history along with the historical and ideological context in which the Dominican saint lived. The second purpose, which I believe is the most important, is to speak out about the philosophical richness of the Thomist theology, peak of the medieval thought, from the reflections on the fiveways that substantiate the existence of God.